The Effect of Advertising on Repatronage Intention with Brand Awareness and Brand Image as Intervening Variable - Luana Auliya Rasmiko; Rohmat Dwi Jatmiko; Khusnul Rofida Novianti (Jamanika (Jurnal Manajemen Bisnis dan Kewirausahaan), 2022)
The purpose of this study was to examine the effect of advertisement on repatronage intention with brand awareness and brand image as an intervening variable at UD. Pari Kuning Banyuwangi. Data was taken using a google form on a sample of 120 respondents using purposive sampling, from the population in the form of consumers who had seen advertisements and visited Pari Kuning agro-business and bistro. Based on the result of path analysis and hypothesis testing, it showed that advertisement, brand awareness, and brand image had a positive and significant effect on repatronage intention. Advertisements had a positive and significant effect on brand awareness and brand image. Brand awareness and brand image can mediate the effect of advertisement on repatronage intention.